2015
DOI: 10.1080/00207543.2015.1092615
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the optimal degree of information sharing in a two-echelon supply chain

Abstract: Information sharing is beneficial for supply chains, but often has marginally decreasing impacts on profit due to the costly expense of collecting more detailed information. This study aims to determine the optimal degree of information sharing with consideration of the trade-off between the cost of collecting information and the benefits gained by utilising it to enhance the profit of a two-echelon supply chain. Based on the analytical results, the profit that the supplier gains from information sharing can s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 32 publications
0
16
0
1
Order By: Relevance
“…Information sharing is an important topic in production and operations research (Chandra, Grabis, and Tumanyan 2007;Daneshvar Kakhki and Gargeya 2019;Lei et al 2019;Shen, Choi, and Minner 2019). Numerous studies have investigated the impacts of information sharing on various SC entities and provided important insights on how to leverage the benefits of information sharing to improve the production and operations systems (Chan and Chan 2009;Chiang and Feng 2007;Davis et al 2011;Huang, Li, and Ho 2016;Wu et al 2011). For instance, Viswanathan, Handik, and Piplani (2007) showed that information sharing with the planned downstream order schedules resulted in the lowest average inventory level for the entire SC.…”
Section: Production Research Literature On Information Sharing Sc Lementioning
confidence: 99%
“…Information sharing is an important topic in production and operations research (Chandra, Grabis, and Tumanyan 2007;Daneshvar Kakhki and Gargeya 2019;Lei et al 2019;Shen, Choi, and Minner 2019). Numerous studies have investigated the impacts of information sharing on various SC entities and provided important insights on how to leverage the benefits of information sharing to improve the production and operations systems (Chan and Chan 2009;Chiang and Feng 2007;Davis et al 2011;Huang, Li, and Ho 2016;Wu et al 2011). For instance, Viswanathan, Handik, and Piplani (2007) showed that information sharing with the planned downstream order schedules resulted in the lowest average inventory level for the entire SC.…”
Section: Production Research Literature On Information Sharing Sc Lementioning
confidence: 99%
“…Dejonckheere et al 2004, Chen and Lee 2009, Trapero et al 2012, Li and Zhang 2015. At the core of collaboration practices lies information sharing (IS), a collaborative mechanism in which the supplier may obtain and utilize the demand and inventory status of the retailer (Huang et al 2016).…”
Section: Contextmentioning
confidence: 99%
“…Making information available to other enterprises and managing the information requires investment in Information Technology (IT) and entails significant resource investments, which could result in a negative cost-benefit analysis (Chan andChan 2010, Kembro et al 2014). Additionally, companies need to bear the risk that information may be leaked intentionally or unintentionally by suppliers (Kong et al 2013, Huang et al 2016. Finally, resulting benefits of IS may be difficult to allocate in a reasonable way among SC partners (Shih et al 2015).…”
Section: Problem Statementmentioning
confidence: 99%
“…Likewise, the data did not include products with a shelf life below 20 days. It should be investigate if sharing point-of-sales and waste data for these more perishable products are sufficient or if sharing more detailed information are needed and profitable to improve the replenishment decision (Huang, Li, and Ho 2015). This additional information may include inventory levels with remaining shelf life or estimated remaining shelf life based on temperature log (Ketzenberg, Bloemhof, and Gaukler 2015).…”
Section: Limitations and Further Researchmentioning
confidence: 99%